ANALISIS PENYEBAB KEJADIAN ANEMIA PADA IBU HAMIL TRIMESTER III - Odilia Esem; Frida S Pay (Jurnal Maternitas Kebidanan, 2023)
Anemia in pregnancy is a health problem that needs global attention. According to WHO anemia during pregnancy reached around 41.8% of people globally in 2008, Asia has the largest prevalence of anemia, with 48.2% of the population (WHO, 2008). Anemia in pregnant women is increasingly common in Indonesia, with prevalence increasing from 37.1% in 2013 to 48.9% in 2018. Many factors cause anemia including social demographics, maternal parity and birth spacing. To analyze the relationship between factors that cause anemia with the incidence of anemia in third trimester pregnant women. This researchis a quantitative descriptive study with a cross sectional approach. The population in this study were all third trimester pregnant women who had their pregnancies checked in April-May 2023 at the Sikumana Health Center, Kupang City, East Nusa Tenggara, totaling 50 people. The sampling technique in this research is total sampling with the same sample size as the population, namely 50 samples.The data collected was analyzed using bivariate analysis (chi square test). Based on the results of the study, it was found that there was a relationship between age and anemia with a p value of 0.000. At the Education levelThere is a relationship between maternal education level and anemia in the third trimester of pregnancyp-valueof 0.000. In economic status, there is a relationship between the economic status of the mother and anemia in the third trimester of pregnancyp-valueas big0.001. The results of the parity analysis showed a relationship between maternal parity and anemia in the third trimester of pregnancyp-valueof 0.000. There is a relationship between maternal birth spacing and anemiap-valueof 0.000. Conclusion:There is a relationship between factors that cause anemia with the incidence of anemia in pregnant women. Suggestion: Pregnant women should pay more attention and care about the problem of anemia, by preparing well before pregnancy planning, so they can avoid anemia problems.